2012
DOI: 10.1007/s10286-012-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nerve activity in stress-induced cardiomyopathy

Abstract: PurposeTo evaluate directly recorded efferent sympathetic nerve traffic in patients with stress-induced cardiomyopathy (SIC).BackgroundSIC is a syndrome affecting mostly postmenopausal women following severe emotional stress. Though the precise pathophysiology is not well understood, a catecholamine overstimulation of the myocardium is thought to underlie the pathogenesis.MethodsDirect recordings of multiunit efferent postganglionic muscle sympathetic nerve activity (MSNA) were obtained from 12 female patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…This is usually measured hours after the initial stressful trigger and catecholamine surge, and so whether it is present immediately during the acute stress remains to be clarified. It is clear that there are abnormalities of peripheral sympathetic nerve function and arterial vasomotor regulation in the aftermath of the acute catecholamine storm 33, [80][81][82] . These vasodilating catecholamines may also activate myocardial β2ARs in addition to vascular β2ARs, and therefore this may reflect a mixed effect.…”
Section: Excessive Transient Ventricular Afterload and Takotsubo Varimentioning
confidence: 99%
“…This is usually measured hours after the initial stressful trigger and catecholamine surge, and so whether it is present immediately during the acute stress remains to be clarified. It is clear that there are abnormalities of peripheral sympathetic nerve function and arterial vasomotor regulation in the aftermath of the acute catecholamine storm 33, [80][81][82] . These vasodilating catecholamines may also activate myocardial β2ARs in addition to vascular β2ARs, and therefore this may reflect a mixed effect.…”
Section: Excessive Transient Ventricular Afterload and Takotsubo Varimentioning
confidence: 99%
“…As one major component of auto-regulatory response to stress, activation of sympathetic nervous system (SNS) is the key trigger of stress-induced cardiovascular disease 4 5 . For example, post-ganglionic muscle sympathetic nerve activity has been reported to contribute to stress-induced cardiomyopathy in post-menopausal women following severe emotional stress 6 . Therefore, activation of SNS could be considered as a potential second hit when combined with other risk factors such as prenatal detrimental exposure contributes to the development of heart disease.…”
mentioning
confidence: 99%
“…All of the subjects in this study underwent microneurography within 72 hours of symptom onset. In contrast, Sverrisdottir and colleagues 54 found that patients with TC had a decrease in MSNA compared with healthy matched controls. This latter study provides less information regarding sympathetic tone during the acute phase of TS because more than half of the subjects were studied in the recovery phase at 1 to 6 months.…”
Section: Microneurographymentioning
confidence: 88%